1, 25-Dihydroxyvitamin D3 inhibits porcine epidemic diarrhea virus replication by regulating cell cycle resumption in IPEC-J2 porcine epithelial cells. (September 2021) - Yang, Jiwen; Tian, Gang; Chen, Daiwen; Mao, Xiangbing; He, Jun; Zheng, Ping; Yu, Jie; Luo, Yuheng; Luo, Junqiu; Huang, Zhiqing; Wu, Aimin; Yan, Hui; et al.
Abstract: Porcine epidemic diarrhea virus (PEDV) infection causes heavy economic losses in the pig industry. Currently, the lack of effective treatments prompts new antiviral researches. We have shown that 25-hydroxyvitamin D3 supplementation alleviated PEDV infection in weaned pigs before. However, it is not clear whether vitamin D inhibits PEDV replication. In this study, 1, 25-dihydroxyvitamin D3 (1, 25(OH)2 D3 ) inhibited PEDV induced mitochondria damage and cell apoptosis. In addition, 1, 25(OH)2 D3 treatment decreased PEDV nucleocapsid gene and protein levels in IPEC-J2 cells. Transcriptomic data showed that PEDV infection altered the expression of 5316 genes (2498 up, 2818 down) in IPEC-J2 cells. The differentially expressed genes were mainly involved in cell cycle process, ribonucleoprotein complex biogenesis, mitotic nuclear division, and other biological processes. Then we examined the effects of PEDV infection on cell cycle progression in IPEC-J2 cells, and the results showed that PEDV induced G0/G1 phase arrest. G0/G1-phase arrest was also conducive to PEDV replication. However, 1, 25(OH)2 D3 treatment decreased G0/G1 phase percentage induced by PEDV. Cyclin D and cyclin E mRNA expression were also increased by 1, 25(OH)2 D3 supplementation upon PEDV infection. Moreover, the regulation of 1, 25(OH)2 D3 on cell cycle progression was abrogated by ERK1/2 inhibitor, as well as the mRNA expression of cyclin D. The inhibition of 1, 25(OH)2 D3 on PEDV replication was also eliminated by ERK1/2 inhibitor. Taken together, these results demonstrated that 1, 25(OH)2 D3 supplementation inhibited PEDV replication, and the anti-virus effect of 1, 25(OH)2 D3 was mediated in part by regulating cell cycle progression through ERK1/2 signaling pathway. Highlights: Porcine epidemic diarrhea virus-induced cell cycle arrest favors self-replication. 1, 25(OH)2 D3 inhibited Porcine epidemic diarrhea virus replication. ERK1/2 was involved in 1, 25(OH)2 D3 inhibition of viral replication and cell cycle arrest. 1, 25(OH)2 D3 alleviated apoptosis and mitochondrial damage.